Tensions and challenges evaluating the impact of entrepreneurship policies - Kantis, Hugo (2020)
Entrepreneurship policies are gaining importance in the policy agenda worldwide. In this context, policy-makers are eager to have more data and information about the effective contribution of such policies and benchmarks, in order to evaluate what worked and what did not. This need for a more evidence-based policy approach has led to a widespread diffusion of impact evaluation techniques, mainly those based on the utilization of complex econometric techniques. However, entrepreneurship, as a systemic and evolutionary phenomenon, calls into question several underlying assumptions and characteristics of such quantitative evaluations. This paper identifies and discusses these challenges and tensions. Based on these reflections, this paper proposes an integrative framework for developing an evaluation and learning system which combines different methodologies and approaches over the policy and its implementation, opening the “black box” of entrepreneurship policy evaluation.